BIODIVERSITAS CYANOBACTERIA DARI BEBERAPA SITU/DANAU DI KAWASAN JAKARTA-DEPOK-BOGOR, INDONESIA - Prihantini, Nining Betawati; Wardhana, Wardhana; Hendrayanti, Dian; Widyawan, Arya; Ariyani, Yuni; Rianto, Ronny (UI Scholars Hub, 2018)
Biodiversity of Cyanobacteria from several ponds/lakes of Jakarta-Depok-Bogor, Indonesia. Research about the exploration on Cyanobacteria diversity from several ponds/lakes of Jakarta-Depok-Bogor area was done. Five research locations were Sunter 2 Lake of North Jakarta, Babakan Pond of South Jakarta, Ulin-Salam dan Agathis Pond at UI Campus of Depok, dan Lido Lake of Bogor. Samples were taken by purposive sampling, and samples analysis using subsample methode. The sampling times were on August to September 2006. Three types of samples which were taken were planktonic samples, epifitic samples, and waters bank soil samples. The results showed that several toxic potential Cyanobacteria were found in several waters, even they were dominant at Sunter 2 Lake dan Agathis Pond (UI Campuss). Based on similarity levels of Cyanobacteria, the five of waters could be classied into 3 group, i.e. Sunter 2 Lake and Agathis Pond, Babakan dan Ulin-Salam Pond, dan Lido Lake. Lido Lake waters was very unique on distribution and diversity of Cyanobacteria. Based on diversity Index (H’) of Cyanobacteria, several waters condition could be catagories as moderate waters, i.e. Babakan, Situ Ulin-Salam, and Situ Agathis Pond. The epifitic and waters bank soil Cyanobacteria which were found were also found as planktonik species except Oscillatoria sp. 3. At least 26 isolate of Cyanobacteria were acquired such as Miicrocystis, Oscillatoria, Gloeocapsa, Merismopedia, Planktothrix, dan Arthrospira.